IPPAR Model Pendekatan Content creator Dalam Mempertahankan Reputasi Di Media Snack Video - Mega Mutia Maeskina; Dasrun Hidayat; Iris Fatia Maharani (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2021)
Maintaining views is a huge responsibility for content creators as it is related to reputation. A successful content creator always attempts to maintain views at minimum viral views. This study aims to investigate the communication behavior of content creators in designing content and how to keep views at a minimum viral view of 5,000 views on Snack Video. This study used an ethnographic study of public relations with the IPPAR analysis model (Insight, Strategic Program, Implementation Program, Action, and Reputation) with a qualitative approach. The results of this study show that 1. Content creators performed phases in designing content by analyzing a situation, building concepts, creating content, and evaluating content in communication behavior, 2. Content creators acted consistently, have genuine ideas, followed viral content, and interacted with the audience in maintaining views. In designing content and maintaining views is related to the reputation and selling value of content creators, so the impact obtained by content creators is support through followers, messages, likes, views, shares, fanbase, and comments from the audience.